Conservatism negatively predicts creativity: a study across 28 countries - Groyecka-Bernard, Agata; Sorokowski, Piotr; Karwowski, Maciej; Roberts, S. Craig; Aavik, Toivo; Akello, Grace; Alm, Charlotte; Amjad, Naumana; Asao, Kelly; Atama, Chiemezie S.; Atamtürk Duyar, Derya; Ayebare, Richard; et al. (SAGE Publications, 2024)
Previous studies have found a negative relationship between creativity and conservatism. However, as these studies were mostly conducted on samples of homogeneous nationality, the generalizability of the effect across different cultures is unknown. We addressed this gap by conducting a study in 28 countries. Based on the notion that attitudes can be shaped by both environmental and ecological factors, we hypothesized that parasite stress can also affect creativity and thus, its potential effects should be controlled for. The results of multilevel analyses showed that, as expected, conservatism was a significant predictor of lower creativity, adjusting for economic status, age, sex, education level, subjective susceptibility to disease, and country-level parasite stress. In addition, most of the variability in creativity was due to individual rather than country-level variance. Our study provides evidence for a weak but significant negative link between conservatism and creativity at the individual level (β = −0.08, p <.001) and no such effect when country-level conservatism was considered. We present our hypotheses considering previous findings on the behavioral immune system in humans. © The Author(s) 2024.